In vitro effect of nanosilver on gene expression of superoxide dismutases and nitric oxide synthases in chicken sertoli cells. (17th September 2014) - Hassanpour, H.; Mirshokraei, P.; Khalili Sadrabad, E.; Esmailian Dehkordi, A.; Layeghi, S.; Afzali, A.; Mohebbi, A.
<x content-type="archive" xml:space="preserve">Abstract</x> To evaluate effects of different concentrations of nanosilver colloid on the cell culture of Sertoli cells, the proportion of lipid peroxidation, antioxidant capacity, nitric oxide (NO) production and genes expression of superoxide dismutases (SOD1 and SOD2) and nitric oxide synthases (eNOS and iNOS) were measured. Sertoli cells were incubated at concentrations of 25, 75 and 125 ppm nanosilver for 48 h. There was progressive lipid peroxidation in treatments according to increasing of nanosilver. Lipid peroxidation, as indicated by malondialdehyde levels, was significantly elevated by the highest concentration of silver colloid (125 ppm), although antioxidant capacity, as measured by ferric ion reduction, was unaffected. Nitrite, as an index of NO production was reduced only in 125 ppm of nanosilver. Expression of SOD1 gene was reduced in nanosilver-treated cells at all concentrations, whereas expression of SOD2 gene was reduced only in cells treated with 125 ppm nanosilver. Expression of iNOS gene was progressively increased with higher concentrations of nanosilver. Expression of eNOS gene was also increased in 125 ppm of nanosilver. In conclusion, toxic effects of nanosilver could be due to high lipid peroxidation and suppression of antioxidant mechanisms via reduced expression of SOD genes and increased expression of NOS genes.